English Language Teaching Textbooks
XV, 373 p.
Keywords: English language teaching textbooks (or coursebooks) play a central role in the life of a classroom. This edited volume contains research-informed chapters focusing on: analysis of textbook content; how textbooks are used in the classroom; and textbook writers' accounts of the materials writing, design, and publishing process.